(untitled) (Comparative & International Education Series, 2022)
There is a growing body of literature recognising the importance of visual methods in social science research and in education (Kara et al. 2021; Mulvihill & Swaminathan, 2019). They encompass a variety of data collection techniques, such as photo/drawing elicitation (Kahu & Pickton, 2020; Brown & Wang, 2013) and various analytical approaches, including interpreting images as text (Reavey, 2011). Non-textual data provides rich experiences from participants and can be used alongside traditional methods, such as interviews for rich data collection and analysis. While drawings/comic storyboards have been explored with school children, less research exists on using visual methods for student employability (Timming, 2017). Our chapter explores how traditional and digital drawings can be used as innovative methods to enrich understanding of student employability. Using data from two recent studies and authors’ reflections, this chapter showcases this participatory approach, presenting the benefits and challenges of application for international student employability research. How to cite in APA: Parry, E., & Zhao, X. (2020). Researcher reflections: Using visual methods to enhance our understanding of employability. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 109-120). STAR Scholars. [order hardcopy ]